On Megatherium gallardoi (Mammalia, Xenarthra, Megatheriidae) and the Megatheriinae from the Ensenadan (lower to middle Pleistocene) of the Pampean region, Argentina - Brandoni, Diego (2008)
The Megatheriinae (Mammalia, Xenarthra, Megatheriidae) are recorded in Argentina from the middle Miocene to the early Holocene. Only the genus Megatherium, comprising several species of controversial validity, is recognized for the Pleistocene of the Pampean region. Megatherium americanum is the best studied species and occurs frequently in sediments assigned to the Lujanian stage (Equus (Amerhippus) neogeus Biozone, c. 0.13-0.08 My). On the other hand, M. gallardoi and M. silenum, both from Ensenadan sediments (Mesotherium cristatum Biozone) of Buenos Aires Province, have been considered by some authors as synonyms of M. americanum. The main goal of this contribution is to complete the description of M. gallardoi, clarify its taxonomic status, and establish its relationships with other megatheriines. Th e most remarkable features of M. gallardoi are: premaxillae not fused to each other or to the maxillae; mandibular ramus relatively low; femur with lateral and medial diaphyseal of the patellar trochlea; humerus and femur robust. Based on the anatomical and comparative analysis, we propose that: 1) M. gallardoi is a valid species; 2) specimen MACN Pv 5002 (holotype of M. gallardoi) is an adult individual; 3) M. gallardoi is related to the clade formed by M. americanum and M. altiplanicum; and 4) M. silenum (the other Megatheriinae known for the Ensenadan Stage of Argentina) should be considered nomen vanum because it lacks diagnostic features and corresponds undoubtedly to a juvenile individual.